(untitled) (Research, Society and Development, 2020)
Temporomandibular disorder (TMD) occurs when there is involvement of the temporomandibular joint (TMJ), masticatory muscles and associated structures. These disorders can result from pain and limitations of mandibular movements, difficulty in chewing, speaking and swallowing. Viscosupplementation of the TMJ with hyaluronic acid (HA) is a minimally invasive method and a therapeutic alternative in cases of pain and mandibular limitation. The aim of this study is to report the evolution of a clinical case of joint TMD refractory to conservative treatment, in a patient with bilateral TMJ pain during mandibular function, tinnitus and crepitation with difficulty opening the mouth. Multidisciplinary follow-up was performed, along with viscosupplementation therapy with hyaluronic acid (VAH) and oral motricity therapy based on mandibular strengthening. They were evaluated after 7 days, 30 days and 60 days, showing satisfactory improvement in 2 months. In conclusion, viscosupplementation associated with exercise-based therapy can be evaluated as effective therapeutic measures for the functional restoration of TMJ and pain reduction. Multidisciplinary treatment in refractory cases of TMD is of paramount importance for the control of signs and symptoms in the long term.